PROBLEM ISSUES OF ADMISSIBILITY OF EVIDENCE, WHICH FORM SECRECY IN CRIMINAL PROCEEDINGS - Денисенко, Г.В. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2022)
Annotation. The article examines the problematic issues of the key features of the definition of evidence that constitutes a secret protected by law in criminal proceedings, admissibility, the determination of the empirical basis of the theoretical and legal regulation of certain categories of evidence and the criteria by which they can be considered admissible when making procedural decisions within the framework of criminal proceedings. It was revealed that there is no unified point of view among scientists regarding the essence of the categories of evidence and the admissibility of evidence that constitute a secret protected by law and must be subjected to a «special» investigation by all participants in criminal proceedings. At the same time, the adoption of legal and justified procedural decisions is possible only when they are based on verified and correctly assessed factual data obtained in accordance with and in the form specified by the Criminal Procedure Code of Ukraine. It has been proven that the admissibility of evidence is a procedural institution, the essence of which is violated in that the appropriate factual data must be obtained together with a source established by law, authorized for this subject of the criminal process and fixed in the manner specified in the criminal procedural law. It is noted that provisions regarding the admissibility of such categories of evidence as those that confirm a secret protected by law have existed in foreign legislation for many years and need to be implemented in domestic legislation. It is justified that the only subject to whose competence is subject the consideration of the completed issue of recognition of the admissibility of evidence should be the court that accepted the trial as part of the criminal proceedings. It is noted that the issue of admissibility of evidence requires further understanding, generalization of existing theoretical studies, development of scientific proposals for improvement of this institute in accordance with international standards.

Анотація. У статті досліджено проблемні питання ключових ознак визначення доказів, які становлять охоронювану законом таємницю у кримінальному провадженні, допустимими, визначення емпіричної основи теоретико-правового регулювання окремої категорії доказів та критеріїв, за яких їх можна вважати допустимими під час прийняття процесуальних рішень в рамках кримінальних проваджень. Виявлено, що серед науковців немає єдиної точки зору щодо сутності категорії доказів та допустимості доказів, які становлять охоронювану законом таємницю, та повинні бути піддані «спеціальному» дослідженню усіма учасниками кримінального провадження. Водночас прийняття законних і обґрунтованих процесуальних рішень можливе лише тоді, коли вони ґрунтуються на перевірених і правильно оцінених фактичних даних, одержаних у відповідності та у спосіб, визначений Кримінальним процесуальним кодексом України. Доведено, що допустимість доказів є процесуальниим інститутом, сутність якого полягає в тому, що належні фактичні дані повинні бути отримані зі встановленого законом джерела, уповноваженим на це суб’єктом кримінального процесу і закріплені у спосіб, зазначеним у кримінально-процесуальному законі. Констатується, що положення щодо допустимості такої категорії доказів, як ті що містять охоронювану законом таємницю, вже багато років існують у зарубіжному законодавстві та потребують імплементації у вітчизняне законодоавство. Обгрунтовується, що єдиним суб’єктом, до компетенції якого належить вирішення підсумкового питання визнання щодо допустимості доказів, повинен бути суд, який здійснює судовий розгляд в рамках кримінального провадження. Зазначено, що питання щодо допустимості доказів потребує подальшого осмислення, узагальнення існуючих теоретичних напрацювань, розробки наукових пропозицій щодо вдосконалення цього інституту відповідно до міжнародних стандартів.
Проблемні питання допустимості доказів, які становлять таємницю у кримінальному провадженні.
Keywords: evidence; admissibility of evidence; secrecy; criminal proceedings; guarantees of secrecy; докази; допустимість доказів; таємниця; кримінальне провадження; гарантії таємниць